2006
DOI: 10.1253/circj.70.1122
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of the Coronary Calcification Score by Multidetector Row Computed Tomography for the Evaluation of Coronary Stenosis in Japanese Patients

Abstract: oronary artery disease (CAD) is the most important cause of death in the industrialized world 1,2 and an efficient noninvasive method of detection is needed. Techniques for measuring coronary artery calcification (CAC) as a marker of atherosclerosis using electronbeam computed tomography (EBCT) have been developed. 3,4 Calcification as assessed by EBCT is associated with atherosclerosis at autopsy and the results of coronary angiography (CAG). 5 Multidetector row computed tomography (MDCT) has become more wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…In addition, a previous study using a hybrid single photon emission computed tomography (SPECT)/CT camera showed that the extent of myocardial perfusion defects tends to worsen as the degree of coronary calcification increases 31) . Furthermore, in a study of 92 patients with 819 segments who underwent invasive CT angiography, the accuracy of a CAC score of 0 was excellent (93%) and a higher number of stenosed vessels was found to be associated with a higher CAC score 32) .…”
Section: Association Between the Cac Score And Prevalence Of Cadmentioning
confidence: 99%
“…In addition, a previous study using a hybrid single photon emission computed tomography (SPECT)/CT camera showed that the extent of myocardial perfusion defects tends to worsen as the degree of coronary calcification increases 31) . Furthermore, in a study of 92 patients with 819 segments who underwent invasive CT angiography, the accuracy of a CAC score of 0 was excellent (93%) and a higher number of stenosed vessels was found to be associated with a higher CAC score 32) .…”
Section: Association Between the Cac Score And Prevalence Of Cadmentioning
confidence: 99%
“…About sixty 3mm-thick slices of the coronary arteries were obtained during a single breath hold (15-20 sec) using prospective ECG-gated axial scanning. Images from the examination were analyzed for the presence and extent of CAC by using coronary calcium quantification software (Aquarius workstation, TeraRecon, Inc., USA) according to the Agatston method [28,29].…”
Section: Measurement Of Coronary Artery Calcification Scorementioning
confidence: 99%
“…3,4 Vascular calcification is very common in end-stage renal disease (ESRD), especially in HD patients. 5 The mechanisms of vascular calcification are hyperphosphatemia and elevated calcium (Ca) × phosphate product. 6,7 Clinical studies have supported the association between vascular calcification and cardiac changes.…”
mentioning
confidence: 99%